Functional Status of Neuronal Calcium Sensor-1 Is Modulated by Zinc Binding - Tsvetkov, Philipp O.; Roman, Andrei Yu.; Baksheeva, Viktoriia E.; Nazipova, Aliya A.; Shevelyova, Marina P.; Vladimirov, Vasiliy I.; Buyanova, Michelle F.; Zinchenko, Dmitry V.; Zamyatnin, Andrey A.; Devred, François; Golovin, Andrey V.; Permyakov, Sergei E.; et al. (Frontiers in Molecular Neuroscience, 2018)
Neuronal calcium sensor-1 (NCS-1) protein is abundantly expressed in the central nervous system and retinal neurons, where it regulates many vital processes such as synaptic transmission. It coordinates three calcium ions by EF-hands 2-4, thereby transducing Ca2+ signals to a wide range of protein targets, including G protein-coupled receptors and their kinases. Here, we demonstrate that NCS-1 also has Zn2+-binding sites, which affect its structural and functional properties upon filling. Fluorescence and circular dichroism experiments reveal the impact of Zn2+ binding on NCS-1 secondary and tertiary structure. According to atomic absorption spectroscopy and isothermal titration calorimetry studies, apo-NCS-1 has two high-affinity (4×106 M-1) and one low-affinity (2×105 M-1) Zn2+-binding sites, whereas Mg2+-loaded and Ca2+-loaded forms (which dominate under physiological conditions) bind two zinc ions with submicromolar affinity. Metal competition analysis and circular dichroism studies suggest that Zn2+-binding sites of apo- and Mg2+-loaded NCS-1 overlap with functional EF-hands of the protein. Consistently, high Zn2+ concentrations displace Mg2+ from the EF-hands and decrease the stoichiometry of Ca2+ binding. Meanwhile, one of the EF-hands of Zn2+-saturated NCS-1 exhibits a 14-fold higher calcium affinity, which increases the overall calcium sensitivity of the protein. Based on QM/MM molecular dynamics simulations, Zn2+ binding to Ca2+-loaded NCS-1 could occur at EF-hands 2 and 4. The high-affinity zinc binding increases the thermal stability of Ca2+-free NCS-1 and favours the interaction of its Ca2+-loaded form with target proteins, such as dopamine receptor D2R and GRK1. In contrast, low-affinity zinc binding promotes NCS-1 aggregation accompanied by the formation of twisted rope-like structures. Altogether, our findings suggest a complex interplay between magnesium, calcium and zinc binding to NCS-1, leading to the appearance of multiple conformations of the protein, in turn modulating its functional status.